Identification and behavioral characteristics of stakeholders of a water diversion project based on ‘sustainable supply chain theory’ - Yali Lu (IWA Publishing, 2021)
The South-to-North Water Diversion project, as one of China's strategic projects, plays an important role in China's development. Sixty-two years after the project was conceived, the central route project began to supply water in 2014. Users along the route are both beneficiaries and project influencers. Their behavior characteristics in the project operation have become a topic worthy of study. In this paper, based on a questionnaire conducted among government departments, enterprises and residents and on stakeholder theory, under the theory model of Sustainable Supply Chain (SSC) around the Triple Bottom Line (TBL) including society, economy and environment, the ecological compensation, sewage treatment and reservoir operation management in Xichuan County were investigated and studied. A total of 289 answers were recovered. Through the survey, it is found that: stakeholders include 15 township governments in Xichuan County, water conservancy project supporting facilities construction companies, ecological industry companies, water supply companies and other enterprises, as well as agricultural growers, rural farmers and non-agricultural residents in Xichuan County. Government stakeholders pursue the development of the overall operation of the project, while enterprises and residents pursue the development of individual economy. Finally, this paper lists the relevant indexes, which provide the opportunity for behavior evolution analysis and sustainable research of the project. HIGHLIGHTS Research into a public welfare water diversion project.; The stakeholders of water diversion project are identified.; Combines water diversion project with sustainable supply chain.; The behavior characteristics of stakeholders are analyzed.; It lays the foundation for later behavior analysis.;